Women and ethnic minorities on boards / Nor Azrina Mohd Yusof - Mohd Yusof, Nor Azrina (Faculty of Accountancy, UiTM Kedah, 2019)
Worldwide, it is argued that women face a glass ceiling when it comes to holding top corporate officer position. This is because they hold so few officer positions, an d hold few board seats. According to MarthurHelm (2006), a glass ceiling means the failure of women and other minority groups in climbing up the corporate ladder, despite seeing the top jobs, they are still not reaching them due to discriminatory barriers . Whilst, Hacker (1951) stated that a minority group is any group of people who because of their physical or cultural characteristics are singled out from the others in the society in which they live for differential and unequal treatment and who therefore regard themselves as objects of collective discrimination. For instance, in Japan, women comprise less than 1% of average board, whereby in Malaysia, in average, there are about 4.2% women on boards. Surprisingly, there were no women on boardroom was foun d in Morocco (Governance Metrics International, 2009). In United States, Adams and Ferreira (2007) found that women only held 13.6% of Fortune 500 board seats in 2003. Furthermore, Bourez (2005) claimed that many firms have only one female director that ca n be regarded as evidence of tokenism. The biggest corporate scandals such as Enron and WorldCom have turned public attention to the composition of corporate boards of directors who are responsible for firm governance (Singh, Terjesen and Vinnicombe, 2008) . This situation is likely to change because boards around the world are under increasing pressure to choose female directors. The extreme promotion of gender diversity occurs in Norway whereby all listed companies must abide by a 40% gender quota for fema le directors or else, they will face delisting (Adams & Ferreira., 2007). According to Randoy, Thomsen and Oxelheim (2006), there are five types of diversity. First, the employee representation on boards. For example, in Norway, employees have the right t o elect 1/3 of the directors if their firms have more than two hundred employees. Employee’s representation adds both to the size and to the diversity of boards. Second, the female board members. By referring to the 448 Scandinavian firms, 14.5% of the boa rd members are women and shareholders elect most of them. Hence, the ratio of female to male board member is roughly 1:7, which is a significant deviation from equality, or 1:1. Third diversity is foreign board members. The fraction of foreign board member s that is 8.4% is relatively low, particularly given that most of the public listed firms in Scandinavia do most of their business internationally and having foreign employees. Fourth, in term of age diversity. A survey conducted among Scandinavian firms r evealed that the average board member in a listed firm 11